2015
DOI: 10.1093/bja/aev062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental oxygen and dexamethasone on surgical site infection: a factorial randomized trial

Abstract: ClinicalTrials.gov number: NCT00273377.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 48 publications
(39 reference statements)
1
94
1
2
Order By: Relevance
“…In fact a recent analysis has demonstrated that subsequent randomized trials could not confirm the conclusions of a majority of earlier meta-analysis studies (71). Ironically the WHO and CDC guidelines rely on a meta-analysis after large clinical trials have failed to demonstrate an advantageous effect of perioperative 80% oxygen (10,17). One may also ask whether studies published in 2000 or earlier reflect present clinical practice, particularly in colorectal or thoracic surgery.…”
Section: * * * Thomas Hachenbergmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact a recent analysis has demonstrated that subsequent randomized trials could not confirm the conclusions of a majority of earlier meta-analysis studies (71). Ironically the WHO and CDC guidelines rely on a meta-analysis after large clinical trials have failed to demonstrate an advantageous effect of perioperative 80% oxygen (10,17). One may also ask whether studies published in 2000 or earlier reflect present clinical practice, particularly in colorectal or thoracic surgery.…”
Section: * * * Thomas Hachenbergmentioning
confidence: 99%
“…The guidelines are based on a meta-analysis and could be a final and conclusive document if there are no more studies coming out after the publication of the guidelines. However, studies on perioperative hyperoxia continue to be published that are at variance with the guidelines (17), and more are to come. We shall not accept guidelines that have weak scientific or statistical support, if any, and that are of very temporary validity, if any.…”
Section: * * * Göran Hedenstiernamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand 7 trials including 2992 patients reported no benefit of 80% inspired oxygen (. Table 1) [2,12,13,15,20,26,28]. The WHO panel members based their recommendations on a meta-analysis of 11 randomized trials of supplemental oxygen during and after general anaesthesia.…”
Section: Adult Patients Undergoing General Anaesthesia With Endotrachmentioning
confidence: 99%
“…The WHO panel members based their recommendations on a meta-analysis of 11 randomized trials of supplemental oxygen during and after general anaesthesia. Using a random effects model, they estimated the odds ratio (OR) for SSI as 0.72 (95% confidence interval CI; 0.55-0.94) in favour of 80% inspired oxygen; however, it is quite unclear why the WHO panel excluded studies by Kurz et al [12] and Anthony et al [2]. The question is critical because including the results of Kurz et al [12] and Anthony et al [2] in the metaanalysis (using the same methodology) yields an OR of 0.84 (CI: 0.62-1.12, p = 0.242), a value that no longer supports this panel's recommendation.…”
Section: Adult Patients Undergoing General Anaesthesia With Endotrachmentioning
confidence: 99%